This was not an accident: An injury prevention primer for emergency and community nurses - Reid, Shelley (Canadian Journal of Emergency Nursing, 2003)
Early one morning in February, Alison, 18 months old, is in the kitchen with her father and two older sisters. While her father is getting the two older children ready for school, Alison reaches up and pulls on the tablecloth. Her father had set his coffee down near the edge of the table; the cup is pulled off. The hot liquid lands on the toddler and scalds parts of her face, shoulder and arm. Alison is taken to the emergency room, where she is treated for second-degree burns. Julian, aged three, is playing in his bedroom while his parents carry grocery bags from the car to the kitchen. After a few minutes, Julian doesn’t answer their calls. He is no longer in his room. He has slipped through the patio door into the pool, to which he gained access via the elevated deck attached to the house. It is only the beginning of May and the water is freezing. Julian is resuscitated and rushed to the emergency department. He is admitted to the intensive care unit where his condition is listed as critical.